Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 decade ago

If f(x) = x + 18, what does f^−1(95) equal?

4 Answers

Relevance
  • Anonymous
    1 decade ago
    Favorite Answer

    First find the inverse function. If f(x) = x + 18, then

    y = x + 18

    y - 18 = x

    x = y - 18

    This means f^-1(x) = x - 18.

    So f^-1(95) is f^-1(95) = 95 - 18 = 77.

  • 1 decade ago

    if f(x) = x + 18

    x = f(x) - 18

    therefore

    f^(-1)(95) = 95 - 18 = 77

  • Rachel
    Lv 4
    1 decade ago

    f^-1(x) = x-18

    so plug in 95 for the x

    95-18 = 77

  • Como
    Lv 7
    1 decade ago

    Let f ( x ) = y and g ( y ) = x

    ie g is inverse of f

    y = x + 18

    x = y - 18

    g ( y ) = y - 18

    g ( x ) = x - 18

    f^(-1) ( x ) = x - 18

    f^(-1) (95) = 95 - 18

    f^(-1) (95) = 77

Still have questions? Get your answers by asking now.